PENGARUH PENGASAPAN TERHADAP KEAWETAN KAYU BINTANGUR (Chalophyllum sp.) DAN KAYU MEDANG (Chinnamomum sp) DARI SERANGAN RAYAP TANAH Coptotermes curvignathus Holmgren - Riki Andika; Farah Diba; Lolyta Sisillia (Tengkawang : Jurnal Ilmu Kehutanan, 2019)
Medang wood (Chinnamumum sp) and Bintangur wood (Calophyllum sp) was used for timber construction even they have low quality on the durability. The efforts need to improve their durability, especially against subterranean termites, the most destructive wood organism. One methods of preservation which can improve the durability was fumigation. Fumigation can be processed with traditional methods and modern methods.  The aim of the study was to improve the durability of Medang wood (Chinnamumum sp) and Bintangur wood (Calophyllum sp)with modern fumigation methods and evaluation the durability against subterranean termites Coptotermes curvignathus Holmgren. Wood sample was measured 2 cm x 2 cm x 1 cm. The fumigation treatment was conducted with oven. The oven size was 1 m x 1 m x 50 cm. Treatments of fumigation consits of 12 hours and 24 hours. The treatment of evaluation the durability agaisnt termites was conducted for 21 days. The wood sample was put on the bottle and 50 termites consist of 45 workers and 5 soldiers were put in the wood sample. The parameter of indicator was termite’s mortality and wood weight loss. Result of the research showed that average termites mortality was reach 100% at wood sample with fumigation method for 24 hours, and 89.2% for wood sample with fumigation method for 12 hours. Meanwhile in control wood the termite’s mortality only 8.6%. The level of termites mortality with fumigation methods for 24 hours was classified very strong and for fumigation methods for 12 hours was classified as strong. The average wood weight loss was 1.21% - 1.30%. This wood weight loss was classified as very low. From the research it is concluded that fumigation method can increased the durability of wood, both on Medang wood and Bintangur wood against the subterranean termites Coptotermes curvignathus Holmgren. The optimal fumigation methods was on 12 hours, both on Medang wood and Bintangur wood.Keywords: Calophyllum sp, Chinnamumum sp, Coptotermes curvignathus, fumigation, wood preservation